The Relationship of Subjective Global Assessment (SGA) with Energy Intake, Protein, Hand Grip Strength and Body Mass Index in Chronic Kidney Disease (CKD) Patients with Continuous Ambulatory Peritoneal Dialysis (CAPD) - Adrianto, Yudhi; Hustrini, Ni Made; Kresnawan, Triyani; Amelia, Annisa Eka; Hudayani, Fitri (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Energy and protein intake in chronic kidney disease (CKD) with continuous ambulatory peritoneal dialysis (CAPD) therapy plays an important role in balancing hypercatabolic conditions. Unbalanced intake will result in energy and protein deficits which are increasing the risk of muscle catabolism, decreasing body mass index (BMI), and malnutrition. Subjective global assessment (SGA) as the gold standard in nutritional assessment is needed in assessing nutritional status and determining malnutrition, therefore nutritional intervention can be delivered and improve CAPD patients’ quality of life. This study was conducted to determine the relationship between SGA with energy and protein intake, hand grip strength, and body mass index on CKD patients undergoing CAPD. Methods. A cross-sectional study was conducted among 30 CKD patients undergoing CAPD which were purposively selected using total sampling. Nutritional status was assessed using SGA questionnaire, energy and protein intake was assessed through food records, and hand grip strength was measured by jamar hydraulic hand dynamometer. The normality of the data was tested using the Kolmogorov-Smirnoff test and bivariate analysis was conducted using the Chi-Square test. Results. Of a total of 30 CKD patients, most of them were aged 25-55 years (76.6%), while the age group <25 years was only>6.7%. More than 73% of patients had normal SGA nutritional status and 26% were malnourished. The average energy requirement was 1,942 (SD 277) Kcal, the lowest energy intake was 921 kcal/day and the highest was 1,959 kcal/day with an average dialysate energy intake of 404 (SD 42) kcal. The average protein intake was 54 (SD 9.5) grams, while the average protein requirement was 70.7 (SD 9.7) grams/day. Based on BMI status, 20% of subjects were underweight, 60% normal, and 20% overweight. A total of 53.3% of patients had poor hands grip strength and only 46.7% were normal with an average grip strength was 26.7 (SD 9.3) kg. Analysis showed that SGA was not related to energy intake (p<0.857), grip strength (p<0.307), and BMI (p<0.829). However, there was a relation between protein intake and SGA (p<0.048, OR: 1.233, 95% CI: 1,058 – 2,389). Conclusions. Inadequate protein intake is related to the risk of malnutrition than adequate protein intake. There is no relationship between energy intake, hands grip strength, and BMI on SGA scores.